A relação entre a educação financeira e empreendedorismo na percepção de jovens estudantes do ensino médio - Zanchet, Talia (2023)
The main objective of this work is to identify the level of financial education that young students have been undergoing, together with their vision and propensity for entrepreneurship. The importance that financial education has in the daily lives of all human beings is undeniable and, therefore, being addressed and discussed even in childhood and adolescence within schools and at home can positively interfere in future decisions to undertake and obtain your own business. Taking into account the scenario currently experienced in the country of debt and consumer default, it is essential to broadly promote the vision of an entrepreneur. To carry out the analysis, young people from the city of Ibiraiaras, aged 17 to 40, were interviewed, where they answered socioeconomic questions and also related to the teaching obtained in schools about entrepreneurship and financial education, as well as private financial and economic analyses. It is concluded that the lack of teaching in schools about entrepreneurship and especially about financial education, is a crucial factor in everyday life in terms of economics. The data shows that almost 80% of those interviewed did not learn anything about financial education, meaning that, even though 95% of those interviewed care about managing their money, around 17% do not usually save monthly. Despite the data presented, young people's desire to learn about financial education exceeds 90%.